SUBSTITUSI TEPUNG UBI JALAR UNGU (Ipomea batatas L) PADA PEMBUATAN BISKUIT CRACKERS - Marlin Lendongan; Thelma Tuju; Lana Lalujan (COCOS, 2017)
ABSTRACTThe objective of this study was to obtain an appropriate formula, preferably from a mixture of purple sweet potato starch and wheat flour through organoleptic test and to analyze the composition of each treatment with 2 (two) times of duplo.The results of organoleptic test biscuit crackers most preferred formula in terms of color, flavor, aroma and crispness is the formula D with a mixture of 25%: 75% purple sweet potato flour and wheat flour. The result of proximate analysis of biscuit crackers for carbohydrate content ranged between 66.73% -70.54%, protein content ranged from 4.46% -7.62%, fat content ranged from 17.40% -18.78%, water content 3.89% -6.62%, ash content 1.63% -3.21% , the calorific value of 454-461.34 kcalKeywords: Biscuit Crackers, Purple Sweet Potato Flour, Wheat Flour.